An efficient semi-analytical method to study the mode I bridging-traction law of composite laminates. (1st September 2021) - Cao, Tiancheng; Zhao, Libin; Wang, Yana; Gong, Xiaojing; Zhang, Jianyu
Abstract: Large scale fiber bridging in composite laminates is one of the most common toughening mechnisms, exerting a close-force on the crack surfaces to restrain the delamination propagation. To account for the effect of the fiber bridging in delamination simulation, a physically semi-analytical method based on the Euler-Bernoulli beam theory considering the bridging stress is presented. The mode I energy release rate for every crack length is explicitly expressed in terms of the external load and bridging-traction parameters, which are iterately identified by the proposed optimization procedure. Based on the presented method, a cohesive zone model integrating the identified bridging-tractions is established to simulate the mode I delamination of three kinds of composite laminates with different interfaces, the numerical results correspond well with the experimental ones, indicating the effectiveness and applicability of the presented method. The delamination morphologies are investigated for better interpretation of the toughening mechanism. The major advantage of the proposed method is that it is efficient and convienient since only basic material properties and experimental load–displacement data of the double cantilever beam specimens are required, without additional parameters measurement with the help of external equipments.